2012
DOI: 10.1186/1746-4358-7-16
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with initiation and exclusive breastfeeding at hospital discharge: late preterm compared to 37 week gestation mother and infant cohort

Abstract: BackgroundTo investigate and examine the factors associated with initiation of, and exclusive breastfeeding at hospital discharge of, late preterm (34 0/7 - 36 6/7 weeks) compared to 37 week gestation (37 0/7 - 37 6/7 week) mother and baby pairs.MethodsA retrospective population-based cohort study using a Perinatal National Minimum Data Set and clinical medical records review, at the Royal Hobart Hospital, Tasmania, Australia in 2006.ResultsLate preterm and 37 week gestation infants had low rates of initiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 21 publications
2
52
2
5
Order By: Relevance
“…The majority of mothers felt they were adequately supported by the breastfeeding consultant and/or by the health care providers during their hospital stay, stated they were satisfied with their experience of breastfeeding and felt comfortable in communicating with health care professionals about breastfeeding. Accordingly, the percentage of infants who were breastfed at discharge in the present study was 94 %, which is higher than previous data published in the literature [2, 4, 5]. This finding could be explained by the fact that, according to the inclusion criteria of the study, all enrolled mothers intended to breastfeed.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…The majority of mothers felt they were adequately supported by the breastfeeding consultant and/or by the health care providers during their hospital stay, stated they were satisfied with their experience of breastfeeding and felt comfortable in communicating with health care professionals about breastfeeding. Accordingly, the percentage of infants who were breastfed at discharge in the present study was 94 %, which is higher than previous data published in the literature [2, 4, 5]. This finding could be explained by the fact that, according to the inclusion criteria of the study, all enrolled mothers intended to breastfeed.…”
Section: Discussioncontrasting
confidence: 77%
“…Despite the potential beneficial effects of breastfeeding in the late preterm population, late preterm infants are at a higher risk of lower initiation of breastfeeding than term infants [2, 4, 5]. Breastfeeding initiation in the U.S. has been reported by Radtke et al [1] to range around 59–70 %.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bar ngton et al 10 reported other factors such as a planned pregnancy, a endance at antenatal classes, vaginal delivery, being accompanied at delivery, and a post-partum hospital stay of >24 hr which were independently associated with mely ini a on of breast feeding in their study. In another study, Ayton et al 11 reported that preterm birth is predic ve of breas eeding failure, with late preterm infants at greater risk of not ini a ng breas eeding and/or exclusively breas eeding at hospital discharge. Certain factors iden fi ed by Agbo et al 12 would serve as mo vators to the working mother to prac ce EBF; these were good family support and longer maternity leave (25.5%).…”
Section: Introductionmentioning
confidence: 95%